Liquidity, Solvency, and Profitability as Determinants of Financial Performance in Indonesian Banking Sub-Sectors - Maula, Siti Inayatul; Janiman Lie (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Banking financial performance plays a crucial role in maintaining economic stability, particularly during the dynamic post-pandemic period. This study aims to analyze the impact of liquidity, solvency, and profitability on the financial performance of banks listed on the Indonesia Stock Exchange for the 2020–2024 period. This study is grounded in agency theory, which explains the relationship between management and shareholders in corporate governance. The research sample consists of 26 banks selected based on specific criteria from a total population of 45. The study employs multiple linear regression analysis using SPSS Statistics 27, supported by classical assumption tests. The results indicate that liquidity has a significant negative effect on financial performance, while solvency and profitability have a significant positive effect.